Produção de mudas e crescimento inicial a campo de Cordia trichotoma submetidas a diferentes condições de irrigação, polímero hidroretentor, sombreamento e umidade do solo - Kelling, Mônica Brucker (2015)
Cordia trichotoma (Vell.) Arrab. ex Steud. species of the Boraginaceae family is considered a priority for logging native tree plantations in southern Brazil, in addition to have an important hole in environmental restoration of degraded areas. However, despite the importance of this species, there are no published reports regarding irrigation and use of water retaining polymers in the production of seedlings, as well as the influence of shading levels and excess soil moisture in early growth in the field, based on morphological and physiological variables. This study was divided into three chapters: Chapter I aimed to define, based on morphological and physiological variables which irrigation blade is indicated, whether or not combined with water retaining polymer doses added to the substrate, in the production of C. trichotoma seedlings, aiming to reduce water consumption. The physiological variables of chlorophyll a fluorescence showed themselves important for behavioral studies of seedlings growth in nurseries. A suitable growth of seedlings in the nursery was obtained with irrigation blades of 4-8-8 mm day-1, alternating it every 60 days, with the possible use of a smaller blade at the start of growth, thereby reducing the consumption of water. The use of a continuous 4 mm day-1 blade in the production of seedlings is possible, since associated with a dose of 3 g L-1 water retaining polymer to the substrate. In Chapter II we evaluated the initial growth for C. trichotoma seedlings in the field under different levels of shading, considering morphological and physiological variables. The aerial part of the plant had the growth negatively influenced in full sun condition. The species responds with great plasticity to different light intensities. However, the shading of 18 and 50% provides favorable growth and physiological values for the early development of the species. The purpose of Chapter III was to identify the effect of excess soil moisture on survival and early growth of C. trichotoma seedlings after field planting, based on morphological and physiological characteristics. The higher content of micropores and clay in successive soil layers (0 to 20 cm) is indicative of the undesirable condition for the survival and early growth of seedlings of C. trichotoma. The species is intolerant to environments with excess soil moisture and the planting is not recommended in plain fields, with drainage problems.